Estudio químico de Aristolochia glossa Pfeifer - Guillén Heredia, Perla (Universidad Michoacana de San Nicolás de Hidalgo, 2020)
The Aristolochiaceae family forms an important part of the biodiversity in Mexico, since some of its species possess a pharmacologic interest. Most of them belong to the genus Aristolochia, which is the only Mexican representative of the family. Aristolochia glossa Pfeifer is one of the plants from this genus widely distributed in Michoacan state, which, until now has not been analyzed from a chemical point of view. Consequently, in the present work, the isolation and identification of their main secondary metabolites of the extracts (apolar and polar) of the roots and aerial parts of the plant were carried out. Neolignans were identified as the major compounds 3-6, and sterols-type terpenes 1 and 2. In addition, chemical modifications were made to corroborate the presence and reactivity of the hydroxyl group in neolignans 5 and 6.

En México la familia Aristolochiaceae forma parte importante de la biodiversidad, ya que algunas especies poseen gran interés farmacológico, la mayoría pertenecen al género Aristolochia, único representante mexicano de la familia. Una especie distribuida en el estado de Michoacán es Aristolochia glossa Pfeifer de la que no existe un estudio químico descrito. En el presente trabajo se realizó el aislamiento e identificación de metabolitos secundarios de los extractos (apolares y polares) de raíz y partes aéreas de la planta. Se identificaron como compuestos mayoritarios los neolignanos 3-6 y terpenos de tipo esteroles 1 y 2, además se llevaron a cabo modificaciones químicas para corroborar la presencia y reactividad del grupo hidroxilo en los neolignanos 5 y 6.
Instituto de Investigaciones Químico Biológicas. Maestría en Ciencias Químicas
Keywords: info:eu-repo/classification/cti/2; IIQB-R-M-2020-0617; Neolignanos; Terpenos; Éster; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/2823